The Effect of Pineapple (Ananas comosus L.) Fruit Extract On The Liver White Rats (Rattus norvegicus) Induced By Soft Drinks - Nur Mawaddha Alfitri; Efrida Pima Sari Tambunan; Syukriah Syukriah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Sparkling-soft drinks are calorie-carbonated drinks that contain a mixture of water, flavorings, and sweeteners. Sparkling drinks contain a lot of artificial sugars which can burden the liver's work to filter toxins. Consuming too many soft drinks can lead to fat buildup that is harmful to the liver. Pineapple (Ananas comosus L.) is a plant rich in calcium, phosphorus, sodium and bromelin enzymes. Pineapple (Ananas comosus L.) also contains vitamin C which functions to stimulate the production of liver enzymes and absorb toxins in the blood circulation that are excreted through the urine. In conditions of impaired liver function, it can be indicated by changes in the levels of Serum Glutamic Oxaloacetic Transminase (SGOT) and Serum Glutamic Pyruvic Transminase (SGPT). The research procedures include plant determination, making pineapple fruit extract, phytochemical screening tests, animal preparation, blood collection and surgery on animals, measuring SGPT and SBOT levels, and data analysis. The purpose of this study was to determine the effect of administration of pineapple fruit extract (Ananas comosus L.) on morphology, SGPT and SGOT levels in the liver of male white rats induced by soft drinks. The study used a complete randomized design method (RAL) with 25 male white rats from 5 groups and 5 replicates, conducted for 30 days, and 7 days of acclimatization. The results of administration of pineapple fruit extract had no significant effect on liver morphology and the dose of 400 mg/kg BB was a good enough dose in reducing SGPT and SGOT levels